2013
DOI: 10.1007/s11605-013-2201-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cold-Stored Vein Allografts for Venous Reconstruction During Pancreaticoduodenectomy

Abstract: The use of fresh vein allografts is a feasible and effective technique for venous reconstruction during pancreaticoduodenectomy. However, prospective surveys including large cohorts of patients are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…This study reported updated results in a larger series of our previously published innovative technique [12], confirming the efficacy and feasibility of using cold-stored venous allografts as patches or conduits for venous reconstruction in pancreatic surgery, especially in case of major venous resections not suitable for primary repair. The rationale of venous resection is to achieve high rates of R0 resections for pancreatic head tumors adherent to the PV or SMV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported updated results in a larger series of our previously published innovative technique [12], confirming the efficacy and feasibility of using cold-stored venous allografts as patches or conduits for venous reconstruction in pancreatic surgery, especially in case of major venous resections not suitable for primary repair. The rationale of venous resection is to achieve high rates of R0 resections for pancreatic head tumors adherent to the PV or SMV.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different native vessels and synthetic grafts have been used to bridge the defect, such as jugular, saphenous or left renal vein [9][10][11]. We previously described the original use of cold-stored vein allografts harvested during the previous 2 weeks from cadaveric donors as a safe option for venous reconstruction after PD [12]. In the current study we reported updated results of this innovative technique, analyzing technical feasibility and postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of venous and arterial homografts, there are very few studies in the literature, the majority having only recently been published with very small cohorts of patients [11,19] . In fact, Meniconi et al [11] have recently described 5 cases of PV and SMV reconstruction using cold-stored vein homografts suggesting that the use of fresh vein homografts is a feasible and effective technique for venous reconstruction during pancreaticoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Meniconi et al [11] have recently described 5 cases of PV and SMV reconstruction using cold-stored vein homografts suggesting that the use of fresh vein homografts is a feasible and effective technique for venous reconstruction during pancreaticoduodenectomy. Adham et al [19] reported the use of cryopreserved arterial homografts in 2 cases for arterial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation